Equilibrium Earnings, Turnover, and Unemployment: New Evidence - Topel, Robert H. (Journal of Labor Economics, 1984)
In labor market equilibrium, sectoral differences in "natural" rates of unemployment generate a conformable distribution of wage differentials that compensate workers for bearing unemployment risk. This paper offers new empirical evidence on the determinants of this equilibrium. The analysis consists of two stages. First, I estimate a three-state model of employment and unemployment that identifies the determinants of individuals' rates of entering and leaving unemployment spells. Sectoral, demographic, and policy-induced differences in unemployment probabilities evolve naturally from this framework. Second, I estimate the impact of these differences on the distribution of wages. An important finding is the powerful impact of the unemployment insurance (UK) system both on unemployment and on equalizing wage differences. The evidence is strong that the availability of UK increases unemployment, while simultaneously reducing the magnitude of compensating wage differentials. Most of the effect of UK on unemployment is due to an increased probability of entering spells of unemployment, mainly temporary layoffs, though the duration of spells is also affected. Neglect of the role of UK as a substitute for wages partially accounts for the small compensating differentials estimated in previous research. In the absence of UK, each point of anticipated unemployment raises an individual's wage by about 2.5%.